2020
DOI: 10.1101/2020.06.17.158105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dog Savior: Immediate Scent-Detection of SARS-COV-2 by Trained Dogs

Abstract: Molecular tests for viral diagnostics are essential to confront the COVID-19 pandemic, but their production and distribution cannot satisfy the current high demand. Early identification of infected people and their contacts is the key to being able to isolate them and prevent the dissemination of the pathogen; unfortunately, most countries are unable to do this due to the lack of diagnostic tools. Dogs can identify, with a high rate of precision, unique odors of volatile organic compounds generated during an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 23 publications
(3 reference statements)
4
24
0
Order By: Relevance
“…An important factor to be carefully analyzed is the collection and the preparation of the experimental samples for the dog's training. Studies testing the skill of dogs to recognize SARS-CoV-2-infected biological samples worked with a relatively small number of independent and single samples (19)(20)(21). This procedure cannot exclude that dogs could memorize the odor of the person, rather than that elicited by the SARS-CoV-2 infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An important factor to be carefully analyzed is the collection and the preparation of the experimental samples for the dog's training. Studies testing the skill of dogs to recognize SARS-CoV-2-infected biological samples worked with a relatively small number of independent and single samples (19)(20)(21). This procedure cannot exclude that dogs could memorize the odor of the person, rather than that elicited by the SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…The authors demonstrated that dogs were able to master the task with high rates of sensitivity (average 82.63%) and specificity (average 96.35%) after a week of training. A third study trained dogs to recognize SARS-CoV-2-infected people from respiratory samples (i.e., saliva, nasopharyngeal swabs or aspirates, and tracheal aspirates) obtained from subjects with mild, moderate, or severe symptomatology ( 21 ). Also, in this case, the results were very promising, with the testing procedure reaching 95.5% sensitivity and 99.6% specificity.…”
mentioning
confidence: 99%
“…Our dogs were able to identify different COVID-19 disease phenotypes and phases of disease expression (sore throat, cough, cold, headache and aching limbs, fever, loss of smell and taste and/or severe pneumonia). Another scent dog detection study conducted by Vesga et al (2020) achieved promising results (95.5% average sensitivity and 99.6% specificity) and also planned real-life experiments 21 . These studies support the evidence of canines offering a reliable screening method for SARS-CoV-2 infections.…”
Section: Discussionmentioning
confidence: 96%
“…Clostridium difficile or mastitis causing pathogens 16,17 , hypoglycaemia in diabetics 18 , and virus infections in cell cultures 12,19 . In addition, several research groups worldwide currently train and deploy SARS-CoV-2 detection dogs 20,21 . In a pilot study, our group showed that dogs were able to detect inactivated saliva samples from COVID-19 patients with a sensitivity of 83% and specificity of 96% 22 , which has been confirmed by other groups training dogs to detect either respiratory secretions or sweat samples from COVID-19 patients 20,21 .…”
Section: Odour Detectionmentioning
confidence: 99%
See 1 more Smart Citation